Perinatal outcome in Patients Presented with Antepartum Hemorrhage - Imtiaz, Raheen; Idrees, Kiran; Samee, Jawairia; Qureshi, Hajra Ali (Indus Journal of Bioscience Research, 2025)
Background: Antepartum hemorrhage is an obstetric complication that can result in unfavorable maternal and perinatal outcomes. Identification and management of APH play an important role in enhancing the survival rates among mothers and neonates. Several factors, such as gestational age, parity, and placental pathology, influence the outcome in cases of APH, yet their association with complication severity is intricate and not fully investigated. Objective: To determine the frequency of perinatal outcomes in patients presenting with antepartum hemorrhage. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from April 2024 to October 2024 at the Department of Obstetrics and Gynaecology, ATH Abbottabad. Methodology: The study included 113 women aged 18-40 years with singleton pregnancies of more than 28 weeks gestation, who presented with APH. Demographic data, including age, gestational age, parity, BMI, and residential status, were recorded. Patients were monitored for perinatal outcomes such as low birth weight, stillbirth, and neonatal death. Results: The study found that 38.9% of participants had low birth weight, 20.4% experienced stillbirth, and 14.2% had neonatal death. Stratified analyses showed that gestational age ≤35 weeks was significantly associated with low birth weight, with a p-value of 0.004. Parity was also significantly associated with low birth weight, as women with fewer previous pregnancies had a higher incidence of low birth weight (p-value = 0.013). For stillbirth, a significant association was found with gestational age ≤35 weeks (p-value = 0.012), but no significant association was found with parity (p-value = 0.213). Conclusion: Our study concludes that antepartum hemorrhage remains a major determinant of adverse maternal and perinatal outcomes.